Internet of things in automotive industries and road safety : electronic circuits, program coding and cloud servers - Singh, Rajesh; Gehlot, Anita; Chimata, Raghuveer; Singh, Bhupendra; Ranjit, P. S. (River Publishers, 2018)
This book provides a platform to readers through which they can access the applications of the'Internet of Things'in the automotive field. Internet of Things in Automotive Industries and Road Safety provides the basic knowledge of the modules--including interfacing--along with the programming. Several examples for rapid prototyping are included to help readers understand the concept of IoT. The book comprises ten chapters for designing different independent prototypes for automotive applications, and it will be beneficial for those who want to get started with hardware based project prototypes. The text is based on the practical experience of the authors while undergoing projects with students and industry.
Keywords: Motor vehicles -- Design and construction.; Traffic safety.; Internet of things.; elektronické knihy; electronic books